Hubungan Tingkat Pengetahuan Pertolongan Pertama Pada Layperson Usia Anak Sekolah Terhadap Efikasi Diri Dalam Penanganan Kasus Cedera : a Systematic Review - Eky Madyaning Nastiti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2020)
Injuries are a serious problem that affects approximately 4.7 million people. The injury rate in Indonesia reached 9.2%, with children included as a vulnerable group. This is related to unsafe environmental conditions and low ability to perform first aid measures. Being able to conduct appropriate action requires courage and self-confidence. One crucial aspect that affects self-efficacy is individual knowledge. This study aims to analyze the correlation between first aid knowledge in school children and self-efficacy in injury management using a systematic review. The research uses two electronic databases: PubMed and Google Scholar and follows the PRISMA (Preferred Reporting Items for Systematic Review and Meta Analyzes) protocol with publications ranging from the years 2010-2020 using seven articles that fit the inclusion and exclusion criteria. The results of the article reviews show that the self-efficacy and the knowledge level of school children about first aid are still low. This relates to the school-age, which is still in the development stage of cognitive and emotional abilities. Furthermore, school children tend to have no previous experience in handling injuries. Thus, efforts are needed to increase self-confidence and knowledge of school-aged laypersons, which can be initiated by health workers. Information obtained from health workers is proven to increase self-efficacy better than other parties. Efforts must be made by considering the methods and media adaptable to this age responsiveness, to increase the number of school-aged laypersons in Indonesia. Keywords: first aid, self-efficacy, knowledge, school children, layperson